Stress-Induced Accumulation of DcAOX1 and DcAOX2a Transcripts Coincides with Critical Time Point for Structural Biomass Prediction in Carrot Primary Cultures (Daucus carota L.) - Campos, M. Doroteia; Nogales, Amaia; Cardoso, Hélia G.; Kumar, Sarma R.; Nobre, Tânia; Sathishkumar, Ramalingam; Arnholdt-Schmitt, Birgit (Frontiers in Genetics, 2016)
Stress-adaptive cell plasticity in target tissues and cells for plant biomass growth is important for yield stability. In vitro systems with reproducible cell plasticity can help to identify relevant metabolic and molecular events during early cell reprogramming. In carrot, regulation of the central root meristem is a critical target for yield-determining secondary growth. Calorespirometry, a tool previously identified as promising for predictive growth phenotyping has been applied to measure the respiration rate in carrot meristem. In a carrot primary culture system (PCS), this tool allowed identifying an early peak related with structural biomass formation during lag phase of growth, around the 4th day of culture. In the present study, we report a dynamic and correlated expression of carrot AOX genes (DcAOX1 and DcAOX2a) during PCS lag phase and during exponential growth. Both genes showed an increase in transcript levels until 36 h after explant inoculation, and a subsequent down-regulation, before the initiation of exponential growth. In PCS growing at two different temperatures (21 °C and 28 °C), DcAOX1 was also found to be more expressed in the highest temperature. DcAOX genes’ were further explored in a plant pot experiment in response to chilling, which confirmed the early AOX transcript increase prior to the induction of a specific anti-freezing gene (AFP). Our findings point to DcAOX1 and DcAOX2a as being reasonable candidates for functional marker development related to early cell reprogramming. While the sequence of gDcAOX2a was previously described, we characterize the complete genomic sequence of DcAOX1.